HW6soln - Homework 6 solutions Section 4.6 page 197-8...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Homework 6 solutions Section 4.6 page 197-8 problem 4: In this case y 1 = e- t , and y 2 = e t . W = y 1 y 2- y 1 y 2 = e- t e t + e- t e t = 2 and v 1 =- Z (2 t + 4) e t 2 dt =- ( t + 1) e t + C 1 v 2 = Z (2 t + 4) e- t 2 dt =- ( t + 3) e- t + C 2 so y = v 1 y 1 + v 2 y 2 =- ( t + 1)- ( t + 3) + C 1 e- t + C 2 e t =- 2 t- 4 + C 1 e- t + C 2 e t . Of course this could also have been computed (more easily) using undetermined coefficients. Problem 6: In this case y 1 = e- t and y 2 = te- t . W = y 1 y 2- y 1 y 2 = e- t ((1- t ) e- t ) + e- t te- t = e- 2 t and v 1 =- Z e- t te- t e- 2 t =- t 2 2 + C 1 v 2 = Z e- t e- t e- 2 t = t + C 2 so y = v 1 y 1 + v 2 y 2 =- t 2 2 e- t + t 2 e- t + C 1 e- t + C 2 te- t = t 2 2 + C 1 + C 2 t ! e- t This problem could also be done with undetermined coefficients. Problem 8: In this case y 1 = cos 3 t and y 2 = sin 3 t W = y 1 y 2- y 1 y 2 = cos 3 t 3 cos 3 t + 3 sin 3 t sin 3 t = 3 and v 1 =- Z sec 2 3 t sin 3 t 3 dt = Z- sin 3 t 3 cos 2 3 t dt =- 1 9 sec 3 t + C 1 , v 2 = Z sec 2 3 t cos 3 t 3 dt = Z sec 3 t 3 dt = 1 9 ln | sec 3 t + tan 3 t | + C 2 so y = v 1 y 1 + v 2 y 2 =- 1 9 sec 3 t cos 3 t + 1 9 (ln | sec 3 t + tan 3 t | ) sin 3 t + C 1 cos 3 t + C 2 sin 3 t = 1 9 (- 1 + sin 3 t ln | sec 3 t + tan 3 t | ) + C 1 cos 3 t + C 2 sin 3 t This problem could not have been done using undetermined coefficients. Problem 22: In this case y 1 = t 2 and y 2 = t 3 W = y 1 y 2- y 1 y 2 = t 2 (3 t 2 )- 2 t ( t 3 ) = t 4 and recalling that the denominator in the formula is aW , where in this case a = t 2 we have v 1 =- Z ( t 3 + 1) t 3 t 6 dt =- Z 1 + t- 3 dt =- 1 + 1 2 t 2 + C 1 = 1 2 t 2 + C 1 , v 2 = Z ( t 3 + 1) t 2 t 6 dt = Z t- 1 + t- 4 dt = ln | t | - 1 3 t 3 + C 2 so y = v 1 y 1 + v 2 y 2 = 1 2 + t 3 ln | t | - 1 3 + C 1 t 2 + C 2 t 3 = 1 6 + t 3 ln | t | + C 1 t 2 + C 2 t 3 Section 4.9 Page 227 Problem 1 1 2 3 4 5 0.2 0.4 0.6 0.8 1.0 M 8 m = 4, k = 1, b = 2 < Section 4.9 Page 227 Problem 2 1 2 3 4 5 0.1 0.2 0.3 0.4 M 8 m = 4, k = 3, b = 3 < Section 5.6 Page 291 Problem 1: To solve, we can use equation (4) on page 287 with the given values, and then use the same trick used in an earlier homework to get the value of I(0) using q(0) and equation (3). Alternately, we can solve using equation (3) in the form L d 2 q dt 2 + R dq dt + 1 C q = E ( t ) using the initial conditions for q(0) and q(0)=I(0). This would give us a formula forusing the initial conditions for q(0) and q(0)=I(0)....
View Full Document

Page1 / 7

HW6soln - Homework 6 solutions Section 4.6 page 197-8...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online